Kewajiban Menuntut Ilmu dalam Hadits - Predi Ari Repi; Zulfahmi Lubis; Misra Nora Dayantri; Sindi Pramita; Ummi Nadrah Nasution (Tarbiatuna: Journal of Islamic Education Studies, 2024)
Seeking knowledge is a necessity that cannot be denied, especially if it is related to one's obligations as a servant of Allah shubhanahu wataala. If we do not understand our obligations as servants. how can we find happiness and security in this world and the hereafter. The research method used by researchers is Library Research, namely studying and searching for information through scientific works, journals, articles, theses, etc. related to related titles. This research resulted that in the book of Sunan Ibnu Majah number 224, this Hadith explains the law of seeking knowledge for every Muslim, male and female, which has been narrated by Imam Ibnu Majah and others. However, this hadith was marked as weak by Imam Syuyuti.